PENGARUH KAI BANDARA YIA TERHADAP MINAT PENGGUNA JASA PENERBANGAN BANDAR UDARA INTERNASIONAL YOGYAKARTA KULON PROGO - Nitis Miftakhul Khasanah; Herida Panji Olivia Azhar (Universitas Sains dan Teknologi Komputer, 2023)
Abstract. KAI YIA Airport is one of the transportation options to Yogyakarta International Airport as a means of supporting transportation to travel to and from Yogyakarta International Airport. This study aims to determine the effect of KAI YIA Airport on the interest of users of flight services at Kulon Progo Yogyakarta International Airport. This research is a quantitative study using non probability sampling, with a sample size of 100 passengers and a error rate of 5%. The data collection process uses a questionnaire and the data analysis used is simple linear regression and the coefficient of determination then the data processing uses the SPSS 26 application. The results of this study indicate that the YIA Airport KAI Variable has a significant effect on the interest of users of Yogyakarta International Airport flight services with sig (0.000<0.05). Then the result of the coefficient of determination obtained 0.173, this means that the influence of KAI YIA Airport on service user interest is 17.3%.